Given the function :
![f(x)=\sqrt[]{x+2}+1](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%5B%5D%7Bx%2B2%7D%2B1)
We need to find each missing value
Given x = -3 , -2 , -1 , 2 , 7
So, substitute with each value of x to find the corresponding value of f(x)
![x=-3\rightarrow f(x)=\sqrt[]{-3+2}+1=\sqrt[]{-1}+1](https://tex.z-dn.net/?f=x%3D-3%5Crightarrow%20f%28x%29%3D%5Csqrt%5B%5D%7B-3%2B2%7D%2B1%3D%5Csqrt%5B%5D%7B-1%7D%2B1)
So, there is no value for f(x) at x = -3 (the function undefined because the square root of -1)
![\begin{gathered} x=-2\rightarrow f(x)=\sqrt[]{-2+2}+1=\sqrt[]{0}+1=0+1=1 \\ \\ x=-1\rightarrow f(x)=\sqrt[]{-1+2}+1=\sqrt[]{1}+1=1+1=2 \\ \\ x=2\rightarrow f(x)=\sqrt[]{2+2}+1=\sqrt[]{4}+1=2+1=3 \\ \\ x=7\rightarrow f(x)=\sqrt[]{7+2}+1=\sqrt[]{9}+1=3+1=4 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%3D-2%5Crightarrow%20f%28x%29%3D%5Csqrt%5B%5D%7B-2%2B2%7D%2B1%3D%5Csqrt%5B%5D%7B0%7D%2B1%3D0%2B1%3D1%20%5C%5C%20%20%5C%5C%20x%3D-1%5Crightarrow%20f%28x%29%3D%5Csqrt%5B%5D%7B-1%2B2%7D%2B1%3D%5Csqrt%5B%5D%7B1%7D%2B1%3D1%2B1%3D2%20%5C%5C%20%20%5C%5C%20x%3D2%5Crightarrow%20f%28x%29%3D%5Csqrt%5B%5D%7B2%2B2%7D%2B1%3D%5Csqrt%5B%5D%7B4%7D%2B1%3D2%2B1%3D3%20%5C%5C%20%20%5C%5C%20x%3D7%5Crightarrow%20f%28x%29%3D%5Csqrt%5B%5D%7B7%2B2%7D%2B1%3D%5Csqrt%5B%5D%7B9%7D%2B1%3D3%2B1%3D4%20%5Cend%7Bgathered%7D)
the graph of the function and the points will be as shown in the following image :
Step-by-step explanation:
1 fourth of dr difference between 2 thirds and 1 half
![-2m^2+4mn-6n^2](https://tex.z-dn.net/?f=-2m%5E2%2B4mn-6n%5E2)
1) Let's write out both expressions subtracting 4m²+2mn+8n² from 2m²+6mn+2n²
![\begin{gathered} 2m^{2}+6mn+2n^{2}-(4m^{2}+2mn+8n^2)_{} \\ 2m^2+6mn+2n^2-4m^2-2mn-8n^2 \\ -2m^2+4mn-6n^2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%202m%5E%7B2%7D%2B6mn%2B2n%5E%7B2%7D-%284m%5E%7B2%7D%2B2mn%2B8n%5E2%29_%7B%7D%20%5C%5C%202m%5E2%2B6mn%2B2n%5E2-4m%5E2-2mn-8n%5E2%20%5C%5C%20-2m%5E2%2B4mn-6n%5E2%20%5Cend%7Bgathered%7D)
2) Note that when we subtract 4m^2 + 2mn + 8n^2 from 2m^2 + 6mn + 2n^2 we need to swap the sign by placing -1 outside the parentheses and then combine like terms adding those terms algebraically.
The equation of this circle in standard form is equal to (x - 4)² + (y - 8)² = 5².
Based on the calculations, the equation of this circle in standard form is equal to (x - 4)² + (y - 8)² = 5²
The equation of a circle.
Mathematically, the standard form of the equation of a circle is given by;
(x - h)² + (y - k)² = r²
Where:
h and k represent the coordinates at the center.
r is the radius of a circle.
The midpoint of the given points represents the center of this circle:
h = (4 + 4)/2 = 4
k = (5.5 + 10.5)/2 = 8
Next, we would determine the radius by using the distance formula for coordinates:
r = √[(x₂ - x₁)² + (y₂ - y₁)²]
r = √[(4 - 4)² + (10.5 - 5.5)²]
r = √[0² + 5²]
r = √25
r = 5 units.
Therefore, the equation of this circle in standard form is equal to (x - 4)² + (y - 8)² = 5².
Learn more about circle here: brainly.com/question/12823137
#SPJ4
Answer:
C) 3/8
37
C) -8 or 8
B) 84.7
D) 7 1/3
Step-by-step explanation:
Think of an absolute value as just ignoring any negative signs.